Utilizando o metódo das características para resolver uma equação diferencial parcial hiperbólica - Gomes, Viviane (2013)
Depth study of the Wave Equation where there was a concern with the deduction of the wave equation for longitudinal vibrations with a dimension, bringing his detailed demonstration by Newton’s Second Law, applying the numerical method of characteristics to solve differential equations with homogeneous wave linear partial examines the second-order equations in two variables, and finally obtaining the Analytical Solution of hyperbolic equations via the method of characteristics comparing with the Numerical Solution.